The implementation of a public education policy - the More Education Program under the look of the coordinators of PME and workshops - Elisangela da Silva Bernado; Bruno Mattos da Silva (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
The main objective of this article is to analyze the implementation of the "Programa Mais Educação" (PME) [More Education Program], through the perceptions and actions of the coordinators of the PME and workshops of two public schools participating in the Program, using interview techniques and field research. Having as theoretical reference the research by Ball, Maguire and Braun (2016) and Michael Lipsky (2019), the study is directed researchers in the field of Public Policy and intends to think of an Educational Policy from the perspective of its agents, who act in this process in the school day to day. This article is the result of a broader research conducted in the city of Rio de Janeiro and a master's dissertation feature of the author. The results point to a great diversity in the implementation of Program in the researched schools that establish relationships with local level of evidence or discretionary power of individuals inserted in the process of implementation of Public Policy, making the normative norms materialize differently.